Small intestine acetylcholinesterase activity in experimental animals exposed to low doses of ionizing radiation - A. S. Anschev (Kazimierz Wielki University, 2020)
Radioactive contamination of the environment has become one of the most important environmental factors and the problem of the possible consequences of the global and rapid change in the level of radiation load on the biosphere for all living things is of particular importance. The objective: to study the activity of AChE in the small intestine of rats - males and females of different ages - both under physiological conditions and under conditions of prolonged γ-irradiation in a total dose of 0.75 Gray. Experimental studies were performed on 510 rats of different ages and sexes of the Wistar line. All animals were kept under standard conditions and on the standard diet of the vivarium. Total γ-irradiation was performed with the use of gamma therapeutic unit "AGAT-R" №83 (isotope 60Co). Analysis of the results showed that the most significant changes in AChE activity underwent in the small intestine of males and females 12 days after the end of the ionizing factor, and for all subsequent stages of the study was characterized by its gradual decrease. Previously unknown pathophysiological mechanisms of violation of the morphofunctional status of the small intestine of offspring obtained from predecessors after chronic γ-irradiation in low doses, the implementation of radiation effects of parental irradiation in their offspring have been obtained. The results of experimental research will provide an opportunity for theoretical justification and practical development of ways of metabolic correction of negative manifestations of radiation-induced damage to the genome in the body of the offspring of irradiated parents. Given the dynamics of changes in acetylcholinesterase activity during the aging of animals, we concluded that prolonged exposure to ionizing radiation at a total dose of 0.75 Gray contributes to the strengthening of involutional changes in the functional state of the small intestine.